Immediate synergistic effect of a trunk orthosis with joints providing resistive force and an ankle–foot orthosis on hemiplegic gait - Katsuhira J (Dove Medical Press, 2018)
Junji Katsuhira,1,2 Sumiko Yamamoto,3 Nodoka Machida,4 Yuji Ohmura,5 Masako Fuchi,6 Mizuho Ohta,7 Setsuro Ibayashi,7 Arito Yozu,8 Ko Matsudaira2 1Department of Prosthetics and Orthotics and Assistive Technology, Faculty of Medical Technology, Niigata University of Health and Welfare, Niigata, 2Department of Medical Research and Management for Musculoskeletal Pain, 22nd Century Medical and Research Center, The University of Tokyo, Tokyo, 3Graduate School of International University of Health and Welfare, Tokyo, 4International University of Health and Welfare, School of Health Sciences at Narita, Department of Physical Therapy, Chiba, 5International University of Health and Welfare, School of Health Sciences at Odawara, Department of Physical Therapy, Kanagawa, 6Department of Occupational Therapy, Kyusyu Nutrition Welfare University, Fukuoka, 7Seiai Rehabilitation Hospital, Fukuoka, 8Center for Medical Sciences, Ibaraki Prefectural University of Health Science, Ibaraki, Japan Purpose: The synergistic effects of a trunk orthosis and an ankle–foot orthosis (AFO) in stroke patients with a hemiplegic gait are unclear. We previously developed a trunk orthosis with joints providing resistive force (TORF) to modify malalignment of the trunk and pelvis and confirmed its positive effects in stroke patients during level walking without an AFO. The aim of the present study was to determine if this trunk orthosis and an AFO have synergistic effects during level walking in community-dwelling patients with chronic stroke. Methods: Twenty-eight community-dwelling stroke patients performed level walking at a self-selected speed with an AFO and again while wearing a TORF (TORF group) or a corset (control group). Spatiotemporal, kinematic, and kinetic data were recorded using a three-dimensional motion analysis system. Results: When compared with the control group, the TORF group showed significant increases in walking speed, number of steps on the paretic leg per minute, and peak ankle plantar flexion moment during the single stance phase. Conclusion: The TORF increased the ankle joint plantar flexion moment at the end of the single stance phase during level walking in stroke patients, leading to an increase in their gait speed because of the modified trunk and pelvis alignment. Keywords: biomechanics, orthosis, gait, stroke, joint moment, motion analysis